SANCHEZ SAINZ, M.; PENNA TOSSO, M. y de la ROSA RODRIGUEZ, B. (2016). Somos como somos. Deconstruyendo y transformando la escuela. Madrid: Los Libros de la Catarata, 191 paginas, ISBN 978-84-9097-178-9. - Adrián Lara Garrido (Universidad de La Rioja, 2019)
SANCHEZ SAINZ, M.; PENNA TOSSO, M. y de la ROSA RODRIGUEZ, B. (2016). Somos como somos. Deconstruyendo y transformando la escuela. Madrid: Los Libros de la Catarata, 191 paginas, ISBN 978-84-9097-178-9.